The Construct of Resilience and its Application to the Context of Political Violence - Benjamin Doty (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
This article is intended to be the first in a series of inquiries into the theory and application of the construct of resilience. The article begins by providing a synopsis of the history, conceptualization, and significance of the construct across various fields of scientific examination. This first section focuses explicitly on the complexity of resilience. The next section follows with a discussion of whether the construct—in light of its most basic and established tenets—is applicable to the context of political violence. It does so by presenting analyses of data collected from youth and young adults living in the conflict-affected regions of Bosnia and Herzegovina and Gaza and the West Bank, Palestine. It is clear from this data that the majority of these individuals reported levels of psychosocial functioning consistent with principles identified in resilience theory.
Keywords: Undergraduate Research; Pursuit